KLAUSULA BAKU PERJANJIAN KREDIT BANK RAKYAT INDONESIA DALAM HUBUNGANNYA DENGAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Oka Mahendra Putra, Ida Bagus; Ari Yuliartini Griadhi, Ni Made (Kertha Semaya : Journal Ilmu Hukum, 2014)
Scientific paper titled “Standard Clause of Bank Credit Agreement Related to the Act No. 8 Year 1999 concerning Consumer Protection”, using empiric writing method. Issues raised in this paper is whether the standard clause of BRI bank credit agreement had complied with the Act No. 8 Year 1999 concerning Consumer Protection and how is the legal consequences if the standard clause of bank credit agreement does not comply with the provisions of article 18 of Act No. 8 Year 1999 concerning Consumer Protection. Based on research, the results are standard clause of bank credit agreement has not been complied with the Act No. 8 Year 1999 concerning Consumer Protection and the legal consequences of the standard clause of bank credit agreements that do not comply with the provisions of the Act No. 8 of 1999 on Consumer Protection is null and void.
Keywords: Standard clause, credit agreement, legal consequences,consumer protection